Análise do efeito do comportamento não linear dos solos em radier estaqueado - Sousa, Mauro Alexandre Paula de (2014)
With the increasing development of large urban centers in the country, the buildings are presenting more audacious forms in respect to the architectural project. The buildings got taller and as a result, the loads imposed to the foundations have also become larger. Knowing this, the concept of piled raft foundations began to be usually employed in many projects. These type of foundations assume that a load portion is supported by the surface layer that is in direct contact with the raft. The piled raft may contain a large number of piles, and some of them bearing high loads and resulting in a pronounced non-linear behavior. Aiming to describe the stress-strain behavior more accurately, a form of nonlinear analysis was implemented in FENF program (Ferramenta Numérica para Análise de Fundações). It is a specific finite element program for 3D foundation analysis of piled rafts. The program was developed at UFG using the language “C” and differs from the others programs by providing a more direct way to access the efforts that the foundation elements are submitted. The dissertation aims to do a literature review of linear and non-linear behavior of foundations and make the implementation of a hyperbolic model for modeling soil behavior. After verifying some literature cases, three different piled rafts (2x2, 4x4 and 6x6) were analyzed considering linear and non-linear soil behavior. The settlement, pile load distribution and internal efforts were compared, discussing the importance of taking into account the non-linear soil behavior.